Sensitivity Enhancement of Group Refractive Index Biosensor through Ring-Down Interferograms of Microring Resonator - Hsuan Lai; Tzu-Ning Kuo; Jia-Yi Xu; Shih-Hsiang Hsu; Yi-Cheng Hsu (Micromachines, 2022)
In recent years, silicon-on-insulator substrates have been utilized for high-speed and low-power electronic components. Because of the high refractive index contrast of the silicon wire, its photonic device footprint can be significantly reduced. Moreover, the silicon photonic process is compatible with a complementary metal-oxide-semiconductor fabrication, which will benefit the high-density optoelectronic integrated circuits development. Researchers have recently proposed using the microring resonator (MRR) for label-free biosensing applications. The high-quality factor caused by the substantial electric field enhancement within the ring makes the MRR a good candidate for biomolecule detection under low analyte concentration conditions. This paper proposes an MRR chip to be a biosensor on the silicon platform through the relative displacement between the spatial ring-down interferograms at various cladding layers. The higher-order ring-down of the spatial interference wave packet will enhance the biosensing sensitivity after optimizing the coupling, MRR length, and the optical source bandwidth at the fixed optical waveguide loss. Finally, a typical sensitivity of 642,000 nm per refractive index unit is demonstrated under 0.1 μW minimum optical power detection for an MRR with a 100 μm radius. Higher sensitivity can be executed by a narrow bandwidth and lower silicon wire propagation loss.